Comprehensive overview of optimizing PV-DG allocation in power system and solar energy resource potential assessments - Raimon O. Bawazir; Numan S. Cetin (Energy Reports, 2020)
Distributed Generation based on Photovoltaic (PV-DG) injected in the power system is considered a highly promising solution due to the advantage of clean energy use. However, the investigation of the optimal PV-DG allocation (site and size) is a significant task for power system requirements and assessment of PV potentials. Recent research works on PV-DG allocation are reviewed from two viewpoints; (1) DG, optimization algorithms and objectives and (2) methodologies of PV potential assessments. Due to the review of recent research works, the research gaps are identified and new methodology will be proposed. The authors strongly believe that this work can be helpful to mitigate power system challenges. Besides, it helps to maximize the PV harness within the power system in particular developing countries.
Keywords: 330; PV-DG; Objective; Optimizing algorithms and PV potentials